Upaya Guru Bk Dalam Mengatasi Perilaku Menyimpang Siswa SMKN 3 Kota Bengkulu - Mutiah, Mutiah (DAWUH : Islamic Communication Journal, 2022)
To find out the Efforts of Bk Teachers in Overcoming Deviant Behavior of Students of SMKN 3 Bengkulu City. Then the researcher will focus on the efforts of the Counseling Guidance Teacher carried out at SMKN 3 Bengkulu City in overcoming deviant behavior in students. This research is motivated by the opinion that deviant actions committed by students can have a negative impact on the teaching and learning process, which affects not only the students concerned but also other people. This research uses descriptive qualitative research which is located at SMKN 3 Kota bengkulu, the author's data sources in this study are the Principal, homeroom teacher, Counseling Guidance Teacher, and Student Council Chairperson as primary data sources with the Counseling Guidance Teacher as the key informant. Books, magazines, internet, reports and documentation as secondary data sources. The data collection methods used were observation, interview and documentation. Data analysis of this research is through data reduction, data presentation and conclusion drawing. The results showed that the efforts of counseling guidance teachers in overcoming deviant behavior of students of SMKN 3 Bengkulu City were by giving warnings to students, providing individual and group guidance, and giving educational punishment to students.